2021
DOI: 10.1101/2021.05.25.21257820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Female Predominant Persistent Immune Dysregulation of the Post COVID Syndrome: A Cohort Study

Abstract: Objective: To describe the clinical data from the first 107 patients seen in the Mayo Clinic Post COVID-19 Care Clinic (PCOCC). Patients and Methods: After IRB approval, we reviewed the charts of 107 patients seen between January 19, 2021 and April 29, 2021 in the Mayo Clinic Post COVID Care Clinic (PCOCC) in order to describe the first 107 patients treated through the Mayo Clinic PCOCC. Data was abstracted from the electronic medical record into a standardized database to facilitate analysis. Phenotypes of pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
1
2
0
1
Order By: Relevance
“…Female sex was associated with having persistent and psychological/mental health symptoms. This is in line with some of the recent reports on long COVID that also found female predominance (Ganesh et al, 2021;Karaarslan et al, 2022;Sudre et al, 2021;Thompson et al, 2021). We found that obesity was associated with long COVID which is consistent with findings by others (Sudre et al, 2021;Thompson et al, 2021).…”
Section: Cpap Continuous Positive Airway Pressuresupporting
confidence: 94%
“…Female sex was associated with having persistent and psychological/mental health symptoms. This is in line with some of the recent reports on long COVID that also found female predominance (Ganesh et al, 2021;Karaarslan et al, 2022;Sudre et al, 2021;Thompson et al, 2021). We found that obesity was associated with long COVID which is consistent with findings by others (Sudre et al, 2021;Thompson et al, 2021).…”
Section: Cpap Continuous Positive Airway Pressuresupporting
confidence: 94%
“…At this time, existing data suggest that patients with persistent symptomatology, including those with fibromyalgia, ME/CFS and POTS, have a dysregulated immune response that may be responsible for the characteristic syndromic presentations. It is highly likely that this pathophysiology also occurs in patients with post-COVID-19 syndrome; indeed, preliminary data from our first 108 patients with post-COVID-19 syndrome does demonstrate an increased incidence of elevation of IL-6 24. More recently, data have emerged demonstrating decreases in CD8+ T cells in patients with PASC compared with healthy controls and patients who had COVID-19 but did not develop PASC 25 26.…”
Section: Discussionmentioning
confidence: 83%
“…It is highly likely that this pathophysiology also occurs in patients with post-COVID-19 syndrome; indeed, preliminary data from our first 108 patients with post-COVID-19 syndrome does demonstrate an increased incidence of elevation of IL-6. 24 More recently, data have emerged demonstrating decreases in CD8+ T cells in patients with PASC compared with healthy controls and patients who had COVID-19 but did not develop PASC. 25 26 Patients with PASC have also demonstrated a significant decrease in T regulatory cells and elevation in the CD14+, CD16+ and CCR5+ monocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…Опубликованы данные о длительном повышении IL-6 (3 и более месяцев) в постковидном периоде и ассоциации данного дисбаланса с симптомами хронической усталости, головной болью и изменением метаболических процессов головного мозга [28] Терапия Арепливиром в остром периоде коронавирусной инфекции позволяет своевременно снизить вирусную нагрузку, что способствует корректировке провоспалительного вектора иммунного реагирова-ния на постковидном этапе и, соответственно, снижает риск прогрессирования атеросклероза, транзиторных нарушений мозгового кровообращения со снижением когнитивных функций, эндотелиальной дисфункции и может рассматриваться в качестве вторичной профилактики сердечно-сосудистых осложнений.…”
Section: Discussionunclassified